Exploring the Link Between Landscape Perception and Community Participation: Evidence from Gateway Communities in Giant Panda National Park, China - Nian Li; Dongmei Gu; Yifei Li; Xinyu Huang; Qibing Chen; Xi Li; Bingyang Lv (Land)
A community landscape is intricately tied to the daily lives and livelihoods of its residents, and it significantly influences human behavior. Community co-management serves as a pivotal approach to fostering the harmonious coexistence between national parks and community dwellers, and it requires the extensive participation of community residents. Accordingly, this study aims to clarify the mechanism by which community landscape perception (LP) affects community participation (CP), with the ultimate goal of promoting widespread engagement. After conducting a survey of 564 residents from three entrance communities in the Sichuan region of the Giant Panda National Park, the data were analyzed using structural equation modeling. The results suggest the following: (1) Cultural landscape and living landscape have a direct impact on CP. The natural landscape can stimulate CP through fostering place attachment (PA) or a sense of responsibility (SR), while the production landscape only influences CP through PA. (2) The cultural landscape plays a crucial role in shaping a sense of belonging and responsibility within a community, while the production landscape is not effective in cultivating an SR. (3) PA can awaken residents’ SR and affect CP, playing a chain mediating role between community LP and CP.